Plant–Soil Interactions Shape Arbuscular Mycorrhizal Fungal Diversity and Functionality in Eastern Tibetan Meadows - Shihu Zhang; Zhengying Yang; Xuechun Yang; Xiaoyu Ma; Qun Ma; Miaojun Ma; Jiajia Zhang (Journal of Fungi)
Arbuscular mycorrhizal (AM) fungi occur in the interface between soils and plants. Yet, the impacts of the plant community functional composition and soil properties on AM fungal communities remain poorly understood in the face of ongoing climate change. Here, we investigated the AM fungal community in alpine meadow habitats of the Tibetan Plateau by linking fungal species richness to plant community functional composition and soil parameters at three latitudinal sites. High-throughput sequencing of the AM fungal small subunit rRNA gene was performed to characterize fungal communities. We found that AM fungal diversity and plant functional diversity, as well as the contents of soil nutrients, were significantly higher in the southernmost site, Hongyuan (HY). Total soil nitrogen and soil-available phosphorus explained the variation in AM fungal diversity, while AM fungal biomass was best predicted by the plant community-weighed mean nitrogen:phosphorus ratio (CWM-N:P). Glomus species preferentially occurred in the northernmost site of Hezuo (HZ). Distance-based redundancy analysis (db-RDA) revealed that AM fungal community structure was influenced by not only CWM-N:P but also by plant community-weighed mean photosynthetic rate (CWM-Pn), soil total carbon, and plant community functional dispersion (FDis). We conclude that plant traits and soil properties are crucial for nutrient–carbon (C) exchange, as fungal symbionts may shape AM communities in this vast alpine meadow ecosystem. Our findings provide timely insight into AM fungal community assembly from the perspective of nutrient–C exchange dynamics in the Tibetan Plateau’s alpine meadow habitats.